(untitled) (Journal of Innovative Research, 2025)
This review article seeks to unveil the multifaceted roles of medical social workers in a multidisciplinary team in hospital settings, uncovering insights from the existing literature highlighting their contribution in promoting holistic patients care outcomes and fostering collaborations and coordination as well as overall functioning of the healthcare system This article reviewed online research articles on the roles of medical social workers within a multidisciplinary team in hospital settings. Keywords used in conducting the literature review were: ‘Medical social workers,’ ‘hospital social workers,’ ‘roles of medical/hospital social workers,’ and ‘multidisciplinary teams in hospital/healthcare settings.’ The Boolean Operator Conjunctive “AND” was employed in the association of these keywords to augment the scope of inquiry. The databases used for literature searches were Google Scholar, ProQuest Central, Semantic Scholar Science Direct, and Research Gate. The articles conclude that medical social workers play vital roles within a multidisciplinary team in hospital settings, such as Service provision, The role of patient advocacy and support, Resources mobilization, the role of discharge planning, and Interprofessional collaboration in chronic disease management within a team. Therefore, it is pertinent that medical social workers are vital members of a multidisciplinary team; their vital roles must be recognized, appreciated, and supported to foster the quality of healthcare provided to patients in a hospital setting.